Moderasi Dalam Pendidikan Islam dan Perspektif Pendidikan Nasional - Muhidin Muhidin; Muhammad Makky; Mohamad Erihadiana (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study is a qualitative research with library research instrument. The data used are qualitative data in the form of descriptions, presentations, and writings relevant to the research topic, which are referred to from books, journals, and articles. This research method is descriptive, which describes data from library materials according to relevant studies. The data was collected using a documentary technique, in which the data was extracted from documents from various library materials, then analyzed using content analysis. With this technique, qualitative data is sorted, categorized (grouped) with similar data. The contents are critically analyzed so that a concrete formulation is formulated which is then explained in depth. The emergence of several phenomena in this country such as the issue of terrorism, Islamophobia, excessive demonstrations, discrimination against one group and blasphemers of religion, made the government realize that Indonesia is a large country that has hundreds of tribes and languages. Ways are needed to maintain that sovereignty, one of which is by providing an understanding in education about the application of moderation in everyday life. Some Islamic values that need to be understood and implemented in the moderation process of Islamic education are: Tawasuth, Tawazun, I'tidal, Tasamuh, Musawah, Shura, Islah, Awlawiyah, Tathawur, Tahaddhur.